Multinational undergraduate team work: Excellence in international capstone projects - Escudeiro, Paula Maria (IOS, 2013)
Enhancing the performance of education systems and reinforcing the international attractiveness of Europe's higher education is one of the flagship initiatives of the Euro 2020 strategy. Multinational Undergraduate Team Work (MUTW) is a capstone project course unit focused on improving the employability of students, which is one of the main priorities of the European Higher Education Area for the decade of 2010 to 2020. The purpose of the MUTW project is to create an environment which encourages the development of students’ soft skills, such as teamwork and communication, in an international setting by means of an innovative instruction paradigm to improve such skills without expensive and extensive curricular changes. This book is drawn from the experiences of the first phase of the MUTW project during the last two years (September 2009 till October 2011). It consists of 10 chapters, covering areas such as motivation, state-of-the-art approaches, communication and negotiation, report writing and oral presentation, open source software, team communication, pilot experience and outcomes and challenges. Providing a comprehensive view of the MUTW paradigm and its surroundings, this book will be of great value to any institution wishing to set up a similar course unit, as well as being of interest to all those involved in multinational collaboration within the education field.